2002
DOI: 10.4315/0362-028x-65.3.515
|View full text |Cite
|
Sign up to set email alerts
|

Control of Natural Microbial Flora and Listeria monocytogenes in Vacuum-Packaged Trout at 4 and 10° C Using Irradiation

Abstract: The effect of gamma irradiation on the natural microflora of whole salted vacuum-packaged trout at 4 and 10 degrees C was studied. In addition, the effectiveness of gamma irradiation in controlling Listeria monocytogenes inoculated into trout was investigated. Irradiation at doses of 0.5 and 2 kGy affected populations of bacteria, namely, Pseudomonas spp., Brochothrix thermosfacta, lactic acid bacteria, H2S-producing bacteria typical of Shewanella putrefaciens, and Enterobacteriaceae, at both 4 and 10 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 32 publications
6
19
0
2
Order By: Relevance
“…[36]. These values obtained in this study are close to the values reported earlier for aquacultured fresh trout from Spain [37,41], Greece [38,39] and U.K [40]. It is widely accepted that the initial microbial load of fresh water varies depending on water conditions and temperature.…”
Section: Resultssupporting
confidence: 78%
“…[36]. These values obtained in this study are close to the values reported earlier for aquacultured fresh trout from Spain [37,41], Greece [38,39] and U.K [40]. It is widely accepted that the initial microbial load of fresh water varies depending on water conditions and temperature.…”
Section: Resultssupporting
confidence: 78%
“…This was in agreement with the works on temperate marine fish (Drosinos et al, 1997;Koutsoumanis and Nychas, 1999) and temperate fresh water fish work of Savvaidis et al (2002) where S. aureus count was 1.2 log 10 CFU gG 1 . All samples registered a 0.2 log reduction counts on the day of sensory rejections which were all within the prescribed limits for fresh dried fish recommended by ICMSF (1986).…”
Section: Microbiological Analysis Changes In Total Viable Counts (Tvc)supporting
confidence: 80%
“…Besides traditional methods involving rapid chilling and ice storage, MAP (Debevere and Boskou 1996;Masniyom et al 2002;Fagan et al 2004) and ionizing radiation treatment (Savvaidis et al 2002) have been used in food preservation giving significant results. MAP treatment improves the food shelf life by means of the use of different gases in the internal atmosphere of the food package: in fact, suitable gas mixtures can retard the microbiological growth (Banks et al 1980;Gibson and Davis 1995) in the fish by creating environmental conditions unfavorable to the microbial growth.…”
Section: Introductionmentioning
confidence: 99%